Preparation method and application of 3D porous honeycomb NiFeP / C hydrogen evolution catalyst

By preparing 3D porous honeycomb NiFeP/C catalysts, using strong interface interaction and multi-stage stratification technology, the problems of low utilization rate and poor conductivity of transition metal phosphide catalysts are solved, and efficient electrocatalytic hydrogen evolution is achieved Performance and stability, suitable for industrial applications.

CN119121284APending Publication Date: 2024-12-13HEILONGJIANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411259940.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing transition metal phosphide catalysts have low active site utilization, poor conductivity in electrocatalytic water decomposition, and their stability and preparation costs need to be optimized to meet industrial application requirements.

Method used

The preparation method of 3D porous honeycomb NiFeP/C catalyst is adopted to improve the activity and stability of the catalyst through strong interfacial interaction and multi-stage layering of solvent-thermal and phosphating pyrolysis, and the built-in between Ni2P and FeP is used. The electric field and the close interface contact accelerate electron transfer.

Benefits of technology

It significantly improves catalytic activity and stability, achieves efficient electrocatalytic hydrogen evolution performance, has high catalytic site density, enhanced electron transfer rate, excellent stability and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121284A_ABST
    Figure CN119121284A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst, and relates to a preparation method and application of a hydrogen evolution catalyst. The technical problems that an existing transition metal phosphide electrode is low in active site utilization rate and poor in catalytic effect are solved. The method comprises the following steps: performing oil removal and hydrophilic treatment on a substrate, loading a Ni precursor on the substrate, loading a Fe precursor on the substrate loaded with the Ni precursor, and finally performing high-temperature phosphorization to obtain the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst. When the hydrogen evolution is carried out in a 0.5 M H2SO4 solution, the overpotential at the current density of 10mA. Cm < 2 > is 78-90mV, and the hydrogen evolution electrode can be used in the field of hydrogen production by electrolyzing water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a hydrogen evolution catalyst. Background Art

[0002] With the increasing depletion of traditional fossil energy, mankind is facing the major challenge of finding efficient, clean and sustainable alternative energy sources. Hydrogen energy is regarded as one of the most promising alternative energy sources due to its high energy density, environmental protection and renewability. At present, water electrolysis hydrogen production technology has become the main method of hydrogen production due to its stability, low pollution and high efficiency. However, the key to improving the efficiency of hydrogen production lies in the development of electrocatalysts with high activity and high stability. Although precious metal catalysts perform well in hydrogen production by water electrolysis, due to their high cost, the industry urgently needs cheap transition metal-based alternatives to achieve economical, effective and stable catalyst development.

[0003] In recent years, transition metal phosphides (TMPs) have shown promising application prospects as potential alternative catalysts for electrocatalytic water splitting, which can be used to catalyze hydrogen evolution (HER) and oxygen evolution (OER) reactions. However, these materials currently have certain defects in their electrocatalytic performance, including low active site utilization, unsatisfactory chemical adsorption and desorption kinetics, and low electron transfer rates. In addition, their stability and preparation cost also need to be further optimized to meet the requirements of industrial applications. Summary of the invention

[0004] The present invention aims to solve the problems of low active site utilization and poor conductivity of existing transition metal phosphide catalysts, and provides a method for preparing a 3D porous honeycomb NiFeP / C (C is carbon paper or carbon cloth) hydrogen evolution catalyst. The method improves the HER activity of the catalyst by strong interface interaction, accelerated electron transfer and synergistic effect of coupling components. The built-in electric field and close interface contact between Ni2P and FeP lead to rapid charge transfer, which can significantly improve the catalytic activity and stability. At the same time, the present invention utilizes multi-level layered solvent thermal and phosphating pyrolysis to achieve precise adjustment of the degree of phosphating, phase composition, morphology and size of the nanostructure. The present invention utilizes a precise and controllable synthesis method and strong electronic interaction between interfaces to greatly improve the conductivity and catalytic site activity of the NiFeP / C hydrogen evolution catalyst, and achieves excellent electrocatalytic hydrogen evolution performance.

[0005] The preparation method of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst of the present invention is carried out according to the following steps:

[0006] 1. First, the carbon paper or carbon cloth is subjected to impurity removal and hydrophilic treatment in sequence, and then ultrasonically cleaned with deionized water to obtain a carbon substrate;

[0007] 2. Add Ni source, urea and ammonium fluoride to solvent I and stir to dissolve to obtain mixed solution I; then transfer the mixed solution I to a reactor, and then immerse the carbon substrate in the mixed solution I in the reactor; seal the reactor and place it in a furnace at a temperature of 120 to 220° C. for 3 to 24 hours to perform a solvent thermal reaction. After the reaction is completed, take out the carbon substrate, wash it and dry it to obtain a precursor I;

[0008] 3. Adding an iron source, an aluminum source, urea and a surfactant to a solvent II and stirring to dissolve to obtain a mixed solution II; then transferring the mixed solution II to a reactor, and then immersing the precursor I in the mixed solution II in the reactor; sealing the reactor and placing it in a furnace at a temperature of 120 to 220° C. for 3 to 24 hours to perform a solvent thermal reaction. After the reaction is completed, taking out the carbon substrate, washing it and drying it to obtain a precursor II;

[0009] Fourth, put the precursor II into a porcelain boat, and place the porcelain boat downstream of the quartz tube furnace, place the phosphorus source upstream of the quartz tube furnace, introduce argon or nitrogen into the quartz tube furnace for protection, and set the temperature of the quartz tube furnace at 2-20℃·min -1 The heating rate is increased to 350-550°C and maintained for 1-5 hours for high-temperature phosphating, and then cooled to room temperature to obtain a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst.

[0010] Furthermore, the method for removing impurities from the carbon paper or carbon cloth in step 1 is one or more of solvent cleaning, alkaline cleaning, electrochemical treatment, plasma treatment and microwave treatment.

[0011] Furthermore, the method for hydrophilic treatment of carbon paper or carbon cloth described in step one is one or more of heat treatment oxidation method, liquid phase treatment method, emulsification cleaning method, ultrasonic cleaning method, electrolytic cleaning method, steam degreasing method and acid cleaning method.

[0012] Furthermore, the Ni source in step 2 is one or more of nickel chloride, nickel nitrate, nickel acetate and nickel sulfate.

[0013] Furthermore, in the mixed solution I described in step 2, the concentration of nickel source is 0.005-0.5 mol / L, the concentration of urea is 0.01-0.3 mol / L, and the concentration of ammonium fluoride is 0.01-0.3 mol / L.

[0014] Furthermore, in the mixed solution I described in step 2, the concentration of nickel source is 0.006-0.024 mol / L, the concentration of urea is 0.015-0.04 mol / L, and the concentration of ammonium fluoride is 0.015-0.03 mol / L.

[0015] Furthermore, in the mixed solution I described in step 2, the molar ratio of the nickel source, urea and ammonium fluoride is 1:(1.3-6):(0.9-5).

[0016] Furthermore, the stirring in step 2 is carried out at a rotation speed of 50 to 500 rpm for 5 to 60 min.

[0017] Furthermore, the solvent I in step 2 is one or more of water, ethanol and methanol.

[0018] Furthermore, the drying temperature in step 2 is 60° C., and the drying time is 6 to 24 hours.

[0019] Furthermore, the Fe source in step three is one or more of ferric chloride, ferric nitrate and nickel sulfate.

[0020] Furthermore, the Al source in step three is one or more of aluminum chloride, aluminum nitrate, aluminum silicate and aluminum sulfate.

[0021] Furthermore, in the mixed solution II described in step three, the concentration of the iron source is 0.005-0.5 moL / L; the concentration of the aluminum source is 0.005-0.5 moL / L; and the concentration of urea is 0.01-0.3 moL / L.

[0022] Furthermore, in the mixed solution II described in step three, the concentration of the iron source is 0.005-0.02 moL / L; the concentration of the aluminum source is 0.005-0.01 moL / L; and the concentration of urea is 0.015-0.04 moL / L.

[0023] Furthermore, in the mixed solution II described in step three, the molar ratio of the iron source, the aluminum source and the urea is 1:(0.3-1.5):(2.0-7.5).

[0024] Furthermore, the molar ratio of the Ni source described in step 2 to the iron source described in step 3 is 1:(0.2-3.5).

[0025] Furthermore, the surfactant described in step three is one or more of hexadecyltrimethylammonium bromide, sodium dodecylsulfonate and polyvinylpyrrolidone.

[0026] Furthermore, in the mixed solution II described in step three, the mass percentage of the surfactant is 1% to 15%.

[0027] Furthermore, the stirring in step 3 is carried out at a rotation speed of 50 to 500 rpm for 5 to 60 min.

[0028] Furthermore, the solvent II in step three is one or more of water, ethanol and methanol.

[0029] Furthermore, the drying temperature in step three is 60° C., and the drying time is 6 to 24 hours.

[0030] Furthermore, the phosphorus source in step 4 is one or both of sodium hypophosphite and trimethyl phosphine.

[0031] Furthermore, the ventilation rate of the argon or nitrogen gas in step 4 is 5 to 100 sccm.

[0032] The 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared by the above method is a self-supporting material based on a carbon paper or carbon cloth substrate.

[0033] The application of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared by the above method is to use the material in hydrogen production by electrolysis of water.

[0034] The 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared by the present invention is a highly efficient hydrogen evolution catalyst. The advantages of this composite material are shown in the following aspects.

[0035] 1. High density of catalytic active sites: The NiFeP / C composite material with 3D porous interconnected structure is precisely controlled by two-step hydrothermal grading. Its surface has more active sites, which helps to significantly improve the rate of catalytic reaction and the adsorption and desorption of water and hydrogen. Enhanced electron transfer rate: The high conductivity of NiFeP / C ensures rapid electron transfer, thereby improving the efficiency of electrocatalytic reaction.

[0036] 2. Precise and controllable synthesis method: Multi-level and layered solvent thermal and phosphating pyrolysis can achieve precise adjustment of the phosphating degree, phase composition, morphology and size of the nanostructure.

[0037] 3. Excellent stability: The composite material exhibits excellent stability under acidic water electrolysis conditions, ensuring reliability for long-term use.

[0038] 4. Low cost and easy preparation: The preparation process of NiFeP / C composite material is relatively simple and low-cost, and has good prospects for industrial application.

[0039] In addition, the NiFeP / C composite material of the present invention has the characteristics of low hydrogen evolution overpotential in acidic electrolyte solution. 2The overpotential is only 78-90 mV (HER) and shows excellent stability. The preparation method of the NiFeP / C composite material of the present invention has the advantages of easy operation, low cost, low equipment investment, high controllability, mild reaction conditions, small footprint and environmental friendliness, and is used in the field of hydrogen production by electrolysis of water. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The XRD pattern of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1;

[0041] Figure 2 This is a scanning electron microscope image of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1;

[0042] Figure 3 This is a scanning electron microscope image of the NiFe / C precursor prepared in Example 1;

[0043] Figure 4 The linear voltammetric scan diagram of the electrode prepared in Example 1;

[0044] Figure 5 The long-term stability of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1 under negative voltage;

[0045] Figure 6 LSV of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1 before and after the stability test;

[0046] Figure 7 The linear voltammetric scanning diagram of the FeP / C composite catalyst prepared in Comparative Example 1;

[0047] Figure 8 The linear voltammetric scan diagram of the Ni2P / C composite catalyst prepared in Comparative Example 2;

[0048] Fig. 9 The linear voltammetric scan diagram of the one-step NiFeP / C composite catalyst prepared in Comparative Example 3;

[0049] Fig.10 is a linear voltammetric scan of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 2;

[0050] Fig.11 is a linear voltammetric scan of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 3; DETAILED DESCRIPTION

[0051] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The various raw materials used in the following embodiments are commercially available unless otherwise specified.

[0052] Example 1: The preparation method of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst of this example is carried out according to the following steps:

[0053] First, the carbon paper was washed with acetone to remove impurities, then soaked in concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1 for 12 h for hydrophilic treatment, and then ultrasonically cleaned with deionized water for 20 min to obtain a carbon substrate;

[0054] 2. Add 1.25g Ni(NO3)2·6H2O, 1.50g urea and 0.65g NH4F into 80mL deionized water, stir for 20min at 300 rpm to dissolve, and obtain mixed solution I; transfer the mixed solution I to a reactor, and immerse the carbon substrate in the mixed solution I in the reactor; seal the reactor and place it in a furnace at 180°C for 12 hours for solvent thermal reaction. After the reaction is completed, take out the carbon substrate, wash it with deionized water 3 times, and then dry it in an oven at 60°C for 12 hours to obtain precursor I;

[0055] 3. Add hexadecyltrimethylammonium bromide to 80 mL of water at a mass percentage of 0.5% to obtain an aqueous solution of hexadecyltrimethylammonium bromide, then add 1.8 g of Fe(NO3)3·9H2O, 1.80 g of Al(NO3)3·9H2O and 2 g of urea to the aqueous solution of hexadecyltrimethylammonium bromide, stir for 20 min at a speed of 300 rpm to dissolve, and obtain a mixed solution II; then transfer the mixed solution II to a reactor, and then immerse the precursor I in the mixed solution II in the reactor; seal the reactor and place it in a furnace at a temperature of 190°C for 24 hours for solvent thermal reaction. After the reaction is completed, take out the carbon substrate, wash it with deionized water 3 times, and then dry it in an oven at a temperature of 60°C for 12 hours to obtain a precursor II;

[0056] Fourth, put the precursor II into a porcelain boat, and place the porcelain boat downstream of the quartz tube furnace, place 0.1g of sodium hypophosphite upstream of the quartz tube furnace, and introduce argon gas into the quartz tube furnace at a ventilation rate of 100sccm for protection. The temperature of the quartz tube furnace was increased by 10℃·min -1 The heating rate was raised to 400°C and maintained for 2 h for high-temperature phosphating, and then cooled to room temperature to obtain a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst.

[0057] The X-ray diffraction spectrum of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1 is as follows Figure 1 As shown, from Figure 1 It can be seen that the components of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst are C substrate, FeP, and Ni2P.

[0058] The scanning electron microscope photograph of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the surface of the electrode sheet is composed of NiFeP / C with a 3D porous network structure with an average pore diameter of 200 to 300 nm. This structure is conducive to the exposure of active sites, the adsorption of water and the decomposition of hydrogen.

[0059] Figure 3 This is a scanning electron microscope image of the precursor II prepared in step 3 of Example 1. Figure 3 It can be seen that precursor II pre-constructs a 3D porous network structure, which provides it with more phosphating sites and ensures the uniformity of phosphating.

[0060] The 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1 was used as the working electrode (cathode) of the electrocatalytic hydrogen evolution reaction, a saturated calomel electrode was used as the reference electrode, and a platinum electrode was used as the counter electrode, and connected to the Chenhua 760e electrochemical workstation. The electrolyte was a 0.5M H2SO4 solution, and the solution was saturated by nitrogen ventilation for 10 minutes at a ventilation rate of 20mL / min. Subsequently, a linear voltammetric test was performed at a scan rate of 2mV / s. The test results show a linear sweep voltammetric curve as shown in Figure 4 Observation Figure 4 It can be seen that the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1 has a current density of 10 mA·cm -2 When , the overpotential of hydrogen evolution reaction is 78mV.

[0061] The long-term stability of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1 under negative voltage is as follows Figure 5 As shown, from Figure 5 It can be seen that after the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst has been continuously operated for 450 hours, the negligible current loss confirms the excellent stability of the electrode. Figure 6 As shown, from Figure 6 It can be seen that the LSV curve of the 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared in Example 1 has almost no deviation before and after the stability measurement, which proves that the catalyst has good chemical stability.

[0062] Comparative Example 1: This comparative example is to prepare a FeP / C composite catalyst, and the specific preparation method is carried out according to the following steps:

[0063] First, the carbon cloth was washed with acetone to remove impurities, then soaked in concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1 for 12 h for hydrophilic treatment, and then ultrasonically cleaned with deionized water for 20 min to obtain a carbon substrate;

[0064] 2. Add cetyltrimethylammonium bromide to 80 mL of water at a mass percentage of 0.5% to obtain an aqueous solution of cetyltrimethylammonium bromide, then add 1.8 g of Fe(NO3)3·9H2O, 1.80 g of Al(NO3)3·9H2O and 2 g of urea to the aqueous solution of cetyltrimethylammonium bromide, and stir for 20 min at a speed of 300 rpm to dissolve to obtain a mixed solution; then transfer the mixed solution to a reactor, and then immerse the carbon substrate in the mixed solution in the reactor; seal the reactor and place it in a furnace at a temperature of 190°C for 24 hours to perform a solvent thermal reaction. After the reaction is completed, take out the carbon substrate, wash it with deionized water 3 times, and then dry it in an oven at a temperature of 60°C for 12 hours to obtain a precursor;

[0065] 3. Place the precursor prepared in step 2 into a porcelain boat, and place the porcelain boat downstream of a quartz tube furnace. Place 0.1 g of sodium hypophosphite upstream of the quartz tube furnace. Pass argon gas into the quartz tube furnace at a ventilation rate of 100 sccm for protection. Set the temperature of the quartz tube furnace at 10 °C min. -1 The heating rate was raised to 400°C and maintained for 2 h for high temperature phosphating, and then cooled to room temperature to obtain a FeP / C composite catalyst.

[0066] The FeP / C catalyst prepared in Comparative Example 1 was directly used as the working electrode (cathode) in the electrocatalytic hydrogen evolution reaction, a saturated calomel electrode was used as the reference electrode, and a platinum electrode was used as the counter electrode. The electrochemical workstation (Chenhua 760e) was connected, and a 0.5 M H2SO4 solution was used as the electrocatalytic electrolyte and the reaction was carried out at 20 mL min -1 Nitrogen was introduced into the solution at a rate of 10 min to saturate the solution with nitrogen. -1 The electrode material was subjected to a linear voltammetric test at a scan rate of , and the obtained linear scanning voltammetric curve was as follows Figure 7 As shown, from Figure 7 It can be seen that the FeP / C composite catalyst prepared in Comparative Example 1 has a high current density of 10 mA·cm 2 The overpotential is 221mV (HER).

[0067] Comparative Example 2: This comparative example is to prepare a Ni2P / C composite catalyst, and the specific preparation method is carried out according to the following steps:

[0068] First, the carbon cloth was washed with acetone to remove impurities, then soaked in concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1 for 12 h for hydrophilic treatment, and then ultrasonically cleaned with deionized water for 20 min to obtain a carbon substrate;

[0069] 2. Add 1.25g Ni(NO3)2·6H2O, 1.50g urea and 0.65g NH4F to 80mL deionized water, stir for 20min at a speed of 300 rpm to dissolve, and obtain a mixed solution; then transfer the mixed solution to a reactor, and immerse the carbon substrate in the mixed solution in the reactor; seal the reactor and place it in a furnace at a temperature of 180°C for 12 hours for solvent thermal reaction. After the reaction is completed, take out the carbon substrate, wash it with deionized water 3 times, and then dry it in an oven at a temperature of 60°C for 12 hours to obtain a precursor;

[0070] 2. Place the precursor prepared in step 2 into a porcelain boat, and place the porcelain boat downstream of a quartz tube furnace. Place 0.1 g of sodium hypophosphite upstream of the quartz tube furnace. Pass argon gas into the quartz tube furnace at a ventilation rate of 100 sccm for protection. Set the temperature of the quartz tube furnace at 10 °C min. -1 The heating rate was raised to 350°C and maintained for 2 h for high-temperature phosphating, and then cooled to room temperature to obtain a Ni2P / C composite catalyst.

[0071] The Ni2P / CP composite catalyst prepared in this comparative example 2 was directly used as the working electrode (cathode) in the electrocatalytic hydrogen evolution reaction, a saturated calomel electrode was used as the reference electrode, and a platinum electrode was used as the counter electrode. The electrochemical workstation (Chenhua 760e) was connected, and a 0.5M H2SO4 solution was used as the electrocatalytic electrolyte and the reaction was carried out at 20 mL min -1 Nitrogen was introduced into the solution at a rate of 10 min to saturate the solution with nitrogen. -1 The electrode material was subjected to a linear voltammetric test at a scan rate of , and the obtained linear scanning voltammetric curve was as follows Figure 8 As shown, from Figure 8 It can be seen that the Ni2P / C composite catalyst prepared in Comparative Example 2 has a high current density of 10 mA·cm 2 The overpotential is 275mV (HER).

[0072] Comparative Example 3: This comparative example is a one-step hydrothermal method to prepare a composite catalyst, and the specific preparation method is carried out according to the following steps:

[0073] First, the carbon cloth was washed with acetone to remove impurities, then soaked in concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1 for 12 h for hydrophilic treatment, and then ultrasonically cleaned with deionized water for 20 min to obtain a carbon substrate;

[0074] 2. Add cetyltrimethylammonium bromide to 80 mL of water at a mass percentage of 0.5% to obtain an aqueous solution of cetyltrimethylammonium bromide, then add 1.8 g of Fe(NO3)3·9H2O, 1.8 g of Al(NO3)3·9H2O, 3.5 g of urea, 1.25 g of Ni(NO3)2·6H2O and 0.65 g of NH4F to the aqueous solution of cetyltrimethylammonium bromide, and stir for 20 min at a speed of 300 rpm to dissolve to obtain a mixed solution; then transfer the mixed solution to a reactor, and then immerse the carbon substrate in the mixed solution in the reactor; seal the reactor and place it in a furnace at a temperature of 190°C for 24 hours for solvent thermal reaction. After the reaction is completed, take out the carbon substrate, wash it with deionized water 3 times, and then dry it in an oven at a temperature of 60°C for 12 hours to obtain a precursor;

[0075] 3. Place the precursor in a porcelain boat, and place the porcelain boat downstream of the quartz tube furnace. Place 0.1 g of sodium hypophosphite upstream of the quartz tube furnace. Pass argon gas into the quartz tube furnace at a ventilation rate of 100 sccm for protection. Set the temperature of the quartz tube furnace at 10 °C min. -1 The heating rate was raised to 400°C and maintained for 2 h for high temperature phosphating, and then cooled to room temperature to obtain a NiFeP / C composite catalyst.

[0076] The NiFeP / C composite catalyst prepared by the one-step hydrothermal method in Comparative Example 3 was directly used as the working electrode (cathode) in the electrocatalytic hydrogen evolution reaction, a saturated calomel electrode was used as the reference electrode, and a platinum electrode was used as the counter electrode. The electrochemical workstation (Chenhua 760e) was connected, and a 0.5 M H2SO4 solution was used as the electrocatalytic electrolyte and the reaction was carried out at 20 mL min -1 Nitrogen was introduced into the solution at a rate of 10 min to saturate the solution with nitrogen. -1 The electrode material was subjected to a linear voltammetric test at a scan rate of , and the obtained linear scanning voltammetric curve was as follows Fig. 9 As shown, from Fig. 9 It can be seen that the Ni2P / CP composite catalyst prepared in Comparative Example 2 has a high current density of 10 mA·cm 2 The overpotential is 173mV (HER).

[0077] Example 2: The difference between this example and Example 1 is that "1.25g Ni(NO3)2·6H2O" in step 2 is replaced by "5.5g Ni(NO3)2·6H2O", and the other steps and parameters are the same as those in Example 1. The obtained 3D porous honeycomb NiFeP / C hydrogen evolution catalyst is recorded as NiFeP / C-1.

[0078] The NiFeP / C-1 hydrogen evolution catalyst prepared in Example 2 was used as the working electrode (cathode) of the electrocatalytic hydrogen evolution reaction, a saturated calomel electrode was used as the reference electrode, and a platinum electrode was used as the counter electrode, and connected to a Chenhua 760e electrochemical workstation. The electrolyte was a 0.5M H2SO4 solution, and the solution was saturated by nitrogen ventilation for 10 minutes at a ventilation rate of 20mL / min. Subsequently, a linear voltammetric test was performed at a scan rate of 2mV / s. The linear sweep voltammetric curve shown in the test results is as follows: Fig.10 Observation Fig.10 It can be seen that the NiFeP / C-1 hydrogen evolution catalyst prepared in Example 2 has a current density of 10 mA·cm -2 When the overpotential of the hydrogen evolution reaction is 85 mV. Compared with the catalyst of Example 1, the decrease in its electrocatalytic hydrogen evolution activity is caused by the fact that the synergistic effect of Ni and Fe active sites due to the larger Ni source slightly deviates from the balance, but compared with the catalysts of Comparative Examples 1 to 3, its catalytic performance is relatively high.

[0079] Example 3: The difference between this example and Example 1 is that the "1.8g Fe(NO3)3·9H2O" in step three is replaced by "6.0g Fe(NO3)3·9H2O", and the other steps and parameters are the same as those in Example 1. The obtained 3D porous honeycomb NiFeP / C hydrogen evolution catalyst is recorded as NiFeP / C-2.

[0080] The NiFeP / C-2 hydrogen evolution catalyst prepared in Example 3 was used as the working electrode (cathode) of the electrocatalytic hydrogen evolution reaction, a saturated calomel electrode was used as the reference electrode, and a platinum electrode was used as the counter electrode, and connected to a Chenhua 760e electrochemical workstation. The electrolyte was a 0.5M H2SO4 solution, and the solution was saturated by nitrogen ventilation for 10 minutes at a ventilation rate of 20mL / min. Subsequently, a linear voltammetric test was performed at a scan rate of 2mV / s. The linear sweep voltammetric curve shown in the test results is as follows: Fig.11 Observation Fig.11 It can be seen that NiFeP / C-2 has a current density of 10 mA·cm -2 When the overpotential of the hydrogen evolution reaction is 90 mV. Compared with the catalyst of Example 1, the decrease in its electrocatalytic hydrogen evolution activity is caused by the fact that the synergistic effect of Ni and Fe active sites due to the large amount of iron source slightly deviates from the balance, but compared with the catalysts of Comparative Examples 1 to 3, its catalytic performance is relatively high.

[0081] The overpotentials of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are listed in Table 1.

[0082] Table 1 Overpotential data of catalysts prepared in Example 1, Comparative Examples 1 and 2

[0083]

[0084] Analysis and comparison of the data in Table 1 show that the composite of Ni2P and FeP brings about strong electron transfer between interfaces, greatly improves the conductivity and catalytic activity, and enhances its catalytic efficiency and stability.

[0085] Example 1 is to prepare a composite catalyst by using multi-level stratified solvent heat and high temperature calcination. The catalyst is a 3D porous honeycomb composite catalyst composed of Ni2P and FeP, which has the best performance. The catalyst can reach 10mA·cm at a negative voltage of only 78mV. -2 Compared with the individual Ni2P and FeP and different ratios of Fe source and Ni source, the NiFeP / C composite catalyst with relatively balanced Ni and Fe sources has better performance, which shows the importance of Ni2P and FeP in the system.

Claims

1. A method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst, characterized in that The method proceeds as follows:

1. First, the carbon paper or carbon cloth is subjected to impurity removal and hydrophilic treatment in sequence, and then ultrasonically cleaned with deionized water to obtain a carbon substrate; 2. Add Ni source, urea and ammonium fluoride to solvent I and stir to dissolve to obtain mixed solution I; then transfer the mixed solution I to a reactor, and then immerse the carbon substrate in the mixed solution I in the reactor; seal the reactor and place it in a furnace at a temperature of 120 to 220° C. for 3 to 24 hours to perform a solvent thermal reaction. After the reaction is completed, take out the carbon substrate, wash it and dry it to obtain a precursor I; 3. Adding an iron source, an aluminum source, urea and a surfactant to a solvent II and stirring to dissolve to obtain a mixed solution II; then transferring the mixed solution II to a reactor, and then immersing the precursor I in the mixed solution II in the reactor; sealing the reactor and placing it in a furnace at a temperature of 120 to 220° C. for 3 to 24 hours to perform a solvent thermal reaction. After the reaction is completed, taking out the carbon substrate, washing it and drying it to obtain a precursor II; Fourth, put the precursor II into a porcelain boat, and place the porcelain boat downstream of the quartz tube furnace, place the phosphorus source upstream of the quartz tube furnace, introduce argon or nitrogen into the quartz tube furnace for protection, and set the temperature of the quartz tube furnace at 2-20℃·min -1 The heating rate is increased to 350-550°C and maintained for 1-5 hours for high temperature phosphating, and then cooled to room temperature to obtain a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst.

2. The method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst according to claim 1, characterized in that: The method for removing impurities from the carbon paper or carbon cloth in step 1 is one or more of solvent cleaning, alkaline cleaning, electrochemical treatment, plasma treatment and microwave treatment.

3. The method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst according to claim 1 or 2, characterized in that: The method for hydrophilic treatment of carbon paper or carbon cloth described in step 1 is one or more of heat treatment oxidation method, liquid phase treatment method, emulsification cleaning method, ultrasonic cleaning method, electrolytic cleaning method, steam degreasing method and acid cleaning method.

4. The method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst according to claim 1 or 2, characterized in that: The Ni source described in step 2 is one or more of nickel chloride, nickel nitrate, nickel acetate and nickel sulfate.

5. The method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst according to claim 1 or 2, characterized in that: In the mixed solution I described in step 2, the molar ratio of the nickel source, urea and ammonium fluoride is 1:(1.3-6):(0.9-5).

6. A method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst according to claim 1 or 2, characterized in that: The solvent I described in step 2 is one or more of water, ethanol and methanol.

7. A method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst according to claim 1 or 2, characterized in that: The Fe source described in step 3 is one or more of ferric chloride, ferric nitrate and nickel sulfate.

8. The method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst according to claim 1 or 2, characterized in that: In the mixed solution II described in step three, the molar ratio of the iron source, the aluminum source and the urea is 1:(0.3-1.5):(2.0-7.5).

9. The method for preparing a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst according to claim 1 or 2, characterized in that: The molar ratio of the Ni source described in step 2 to the iron source described in step 3 is 1: (0.2-3.5).

10. Application of a 3D porous honeycomb NiFeP / C hydrogen evolution catalyst prepared by the method of claim 1, characterized in that: The application is to use D porous honeycomb NiFeP / C hydrogen evolution catalyst in hydrogen production by water electrolysis.

Citation Information

Cited By

  • Preparation method of Fe2O3-based hydrogen evolution catalyst

    CN122543097A